Innovation and Technology Policy (ITP) for catching up : a three phase life cycle framework for industrializing economies - Avnimelech, Gil (CEPAL Buenos AiresAR, 2007)
Outlines a dynamic, medium/long term Innovation and Technology Policy framework for industrializing economies directed to simulate innovation and to contribute to the eventual creation of high impact entrepreneurial clusters.